TECHNICAL AND ECOLOGICAL PROPERTIES OF SETAPRET PFF USED IN THE LIGHT INDUSTRY (International Conference on Medical Science, Medicine and Public Health, 2025)
This article analyzes the ecological and technical aspects of the Setapret PFF substance in modern textile industry. Setapret PFF is a fluorocarbon-free water-repellent finishing agent that meets international environmental standards such as OEKO-TEX® Standard 100, ZDHC, and Bluesign. The study covers its application areas, technological parameters, and environmental safety.